PENGARUH PENGANGGURAN, PERTUMBUHAN EKONOMI DAN INDEKS PEMBANGUNAN MANUSIA (IPM) TERHADAP KEMISKINAN DI KABUPATEN PAKPAK BHARAT - Rahmah, Mutia; Berutu, Setia Kawan; Yurina, Yurina (Jurnal Ekonomi Regional Unimal, 2023)
This study examined the effect of unemployment, economic growth and human development index (HDI) on poverty in the Pakpak Bharat Regency. This study used time-series data from 2006 to 2020. The method of data analysis used was multiple linear regression using Eviews10. The results partially indicated that unemployment positively and significantly affected poverty in Pakpak Bharat Regency, Economic Growth Positively but insignificantly affected poverty in Pakpak Bharat Regency, and Human Development Index Positively but insignificantly affected poverty in Pakpak Bharat Regency. Simultaneously, Unemployment, economic growth and the human development index influenced poverty. The test results obtained from the R2 value concluded that the Adjusted R-square value in this study was 0.659, which indicated that the variables of TPT, Economic Growth, and HDI influenced poverty by 65.9% while the other 34.1% was influenced by variables outside the study.